MARXIST CRITICISM ON DISNEY’S MOVIE CINDERELLA - Hira, Muhamma Faizal (LANTERN (Journal on English Language, Culture and Literature), 2017)
Cinderella is a film made by Walt Disney based on European folk tale written by Charles Perrault in 1697. The film depicts the story of a girl who is bound by the oppressive behavior of the stepmother and step- sisters, who in continuation she wanted to change her fate in a single night. This book analyzes the film with marxist point of view. This book discussed about the class struggle, class and status, and false conciousnesswithin the movie. The author uses theories of Karl Marx to analyze the elements that contained in this film. In this analysis we can conclude that Cinderella is not just a regular animated movie but a movie full of Marxist elements.